Pemberdayaan Kelompok Wanita Tani Dalam Mengolah Produk Pasca Panen Minuman Sereh Lemon Selasih - Tohiroh, Tohiroh; Saefullah, Aep; Nurdin, Nurdin; Sukardi, Sukardi; Mulasih, Siti; Syahreza, Arief; Lesmana, Asep Surya; Rahmi, Cinta; Amalia, Fisy; Pardian, Ramadani; Candra, Hendra; Saksana, Joned Ceilandra; Noor, M. Arief (LPPM STIE Ganesha, 2024)
This community service aims to empower women's farmer groups in processing post-harvest products, specifically lemongrass lemon basil drink. The target of this activity is the Garuda RW 12 Women's Farmer Group in Cipayung Village, Ciputat District, South Tangerang City, which has great potential in developing processed products from local agricultural produce. The activity was conducted on Sunday, May 19, 2024, at the RW 12 Hall Office and the local garden. The method used in this activity includes intensive training and mentoring, covering the stages of planning, implementation, and evaluation. The training encompasses processing techniques, packaging, and marketing strategies for the lemongrass lemon basil drink product. The results show that the women's farmer group can process lemongrass lemon basil drink with good quality standards. Additionally, there was an increase in the knowledge and skills of group members in technical and managerial aspects. The products also received positive feedback from the local market, reflected in increased sales and consumer interest. The implications of this activity are the enhancement of the economic welfare of the women's farmer group through the diversification of post-harvest processed products and the strengthening of their capacity to develop small-scale agricultural-based businesses. This empowerment is expected to serve as a model that can be applied in other villages with similar conditions